Tectónica del detalle arquitectónico y su didáctica en el taller de proyecto - Busnelli, Roberto Rafael (2022)
We live in an online world. Everything is immediate, visual. The images replace the reality they represent. Mc Luhan's old proclamations now crystallize on the facades of buildings, which become physically interactive visual supports: the medium is the message and the matter, the image. During the last decades, we have been able to verify an overvaluation of visual culture, which has led to scenographic excesses in architectural works considered paradigmatic. This overvaluation has moved its point of attention away from the physical, ontological value, displacing the constructive logic for the logic of the image and the media appearance.\nArchitecture schools have not been immune to this overvaluation of visual culture. The reality, in our country, indicates that, thanks to a teaching model that has been in charge of separating the project strategies from the knowledge of the material and technical field, a lack of integration has been generated between these two fields of knowledge, which has led to the need to requalify and refine the relationships established between them. In this context, it is necessary to reorient our practice, and the way of teaching, towards the construction of a material culture of the architecture project.\nThe overall ensemble of the architectural work is closely integrated to the details, its design and its quality. Understood in this way, the detail affects the spatial and general values of the whole. Within the process of materialization of an idea, the importance of architectural detail, with its different approaches and material discourses, is essential, as long as the type of architecture to be made is clear, that is, not as the consequence of a resolution eminently technical, but as a consequence of the integration between the projectual and technical-material fields.\nThis doctoral thesis proposes a didactics for the project workshop that, in parallel to the development of the consecrated categories of the project process, incorporates a series of new dimensions that challenge, in stages, the material condition during the project process. This thesis supports the importance of considering the architectural detail as an integrating space of the project, material, technical and construction aspects and thus recovering its value within the realization of the shape-shaping procedure in its various versions, from classical composition, experimentation and project research. This recovery and enhancement of the tectonics of the architectural detail will collaborate with the recovery of a material culture of the architectural project, which makes it possible to give meaning to the action and contextualize its transformation process.